Doa search and retrieval using N-Gram / Nur Nabilah Abu Mangshor ... [et al.] - Abu Mangshor, Nur Nabilah; Sabri, Nurbaity; Ibrahim, Zaidah; Kasiran, Zolidah; Ahmad, Anis Safura (Penerbit UiTM (UiTM Press), 2017)
‘Doa’ is derived from Arabic word which means that one asks for the fulfillment or a need or the cure of sickness from him/her. Having to search and retrieve the relevant ‘doa’ for one needs at any particular time is beneficial. There are some search and retrieval applications that require using the exact match of the keyword search with the words stored in the database. This approach leads to the retrieval of insignificant results as users need to know the exact word to be searched. Therefore, this project allows for partial keyword search that utilises N-gram method for the search and retrieval process. Moreover, various words may have similar meaning thus to increase the accuracy of the retrieved result, this project compares the dice and overlap coefficient algorithms to find the synonyms of the searched word. The result produced indicatesthat overlap coefficient perform better than dice coefficient.